Effect of Gambir Catechins in Modulating the Amyloid-\(β\) Concentration in Cerebrospinal Fluid of Alzheimer’s Model Rat - U. U. Fasrini; N. I. Lipoeto; Z. Taufiqa (Medical Research and Its Applications Vol. 10, 2024)
Background: Alzheimer’s disease [AD] is the most common type of dementia, a neurodegeneration disorder. Neurodegeneration in Alzheimer’s disease has been reported as the consequence of amyloid-\(β\) accumulation in the brain resulting from oxidative stress. Gambir, which contains catechins as a potential antioxidant, is abundant in West Sumatra. Research is scarce about gambir catechins and their potential as anti-amyloid therapeutics. Aim: This study aims to evaluate the effect of gambir catechins administration on amyloid-\(β\) concentration in cerebrospinal fluid [CSF] of the rats. Methods: An experimental study with a post-test-only design was carried out on 12-week-old female Sprague Dawley, an Alzheimer’s model rat. As many as 30 rats were divided into the control and treatment groups. Four of the six groups were treated with the catechins extract doses of 20 mg, 40 mg, 60 mg, and 100 mg per 200 g BW. The gambir catechin extracts were purchased from the Andalas Phytopharmacy Laboratory. Meanwhile, the other two groups were positive and negative control groups. After four weeks, the rats were sacrificed and the CSF was collected. Amyloid-\(β\) concentration measurement was done using the ELISA method. The statistical analysis was using One-way ANOVA with posthoc test Tukey HSD. Treatment groups exhibited a linear decrease in amyloid-\(β\) concentration in all doses, particularly in CC3. Results: The CC3-treated group showed the lowest amyloid-\(β\) concentration [13.325\(±\)4.625 ng/ml], which is significantly lower [p<0.05] when compared to the PC group [45.280\(±\)7.590 ng/ml]. In the present study, the decrease of A\(β\)-42 peptide concentration in the CC3 group compared to the PC group is the most significant. Conclusion: This result provides experimental evidence that gambir catechin reached its optimum neuroprotective effect on amyloid-\(β\) level in cerebrospinal fluid by 60 mg/200 g BW.